2021
DOI: 10.1155/2021/8898671
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Central Diabetes Insipidus and Acute Myeloid Leukemia

Abstract: Central diabetes insipidus (CDI) is a rare reported complication of acute myeloid leukemia (AML). The onset of AML-associated CDI often precedes the diagnosis of AML by weeks or months and is considered an adverse prognostic indicator in this setting. The mechanism of AML-associated CDI is not known; however, it is often reported in the setting of cytogenetic events resulting in MDS1 and EVI1 complex locus protein (MECOM) gene overexpression. Here, we describe a case of new onset CDI which preceded a diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The combination of AML and DI is unique, and the diagnosis of DI is mostly made either before the diagnosis of AML or at the time of diagnosis of AML [ 2 , 6 ]. DI with AML is typical of pituitary origin which is supported by the fact that many patients respond to desmopressin [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of AML and DI is unique, and the diagnosis of DI is mostly made either before the diagnosis of AML or at the time of diagnosis of AML [ 2 , 6 ]. DI with AML is typical of pituitary origin which is supported by the fact that many patients respond to desmopressin [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, CDI with AML is an unfavorable association and some reports have documented poor clinical outcomes [ 2 , 6 , 16 ]. Intensive induction chemotherapy and allogeneic stem cell transplantation have been proven to be beneficial in prolonging survival in a few cases [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient’s robust improvement in symptoms and biochemistry with desmopressin therapy along with her MRI findings suggested a central rather than nephrogenic cause for her DI. CDI has been uncommonly seen in association with AML, with approximately 100 case studies reported worldwide ( 2 , 5 ). When present, it has largely been observed with aberrations in chromosomes 3 and 7 ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the most likely mechanism for the development of CDI and partial anterior pituitary dysfunction is leukemic infiltration, with hemorrhage, infection, or thrombosis of the small vessels of the hypophysis ( 3 , 5 , 7 ). Supporting evidence includes the time course of her presentation with respect to her AML diagnosis, imaging findings, and investigations excluding other causes.…”
Section: Discussionmentioning
confidence: 99%